2022
DOI: 10.1002/gps.5810
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in older COVID‐19 patients: Evaluating risk factors and outcomes

Abstract: Objectives: A high incidence of delirium has been reported in older patients with Coronavirus disease 2019 . We aimed to identify determinants of delirium, including the Clinical Frailty Scale, in hospitalized older patients with COVID-19. Furthermore, we aimed to study the association of delirium independent of frailty with in-hospital outcomes in older COVID-19 patients. Methods:This study was performed within the framework of the multi-center COVID-OLD cohort study and included patients aged ≥60 years who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Further factors previously reported to increase the likelihood of delirium in COVID-19, but not assessed in our study, comprise frailty, alcoholism, smoking, and polypharmacy [ 9 , 10 , 29 ]. For instance, it has been previously shown that delirium does not represent an independent predictor of mortality in frail patients with COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further factors previously reported to increase the likelihood of delirium in COVID-19, but not assessed in our study, comprise frailty, alcoholism, smoking, and polypharmacy [ 9 , 10 , 29 ]. For instance, it has been previously shown that delirium does not represent an independent predictor of mortality in frail patients with COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional finding of our study is that having COVID-19 and delirium was significantly associated with increased LOS as compared with COVID-19 alone. The relationship between delirium and LOS has been evaluated in other studies, which have demonstrated that the LOS was longer in patients with a COVID-19 diagnosis who developed delirium,20,21,25 with one study demonstrating a median LOS approximately 1.5 times greater21 and a second study demonstrating no change 26…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a positive association with in-hospital mortality among older patients with COVID-19. 20,[22][23][24][25][26][27] However, other studies looking specifically at mortality in patients with delirium have shown mixed results. Ticinesi and colleagues 27 demonstrated significantly higher mortality in patients who developed delirium during hospitalization than those who did not (57% vs 30%, P < .001), while another reported delirium was not associated with higher mortality.…”
Section: Delirium and In-hospital Mortalitymentioning
confidence: 99%
“…It mainly affects frail older adults and severely ill patients and is associated with increased risk on adverse clinical outcomes 2 . Delirium also plays a significant role in the context of older patients hospitalised for Coronavirus disease 2019 (COVID‐19) and its estimated prevalence is between 14.2% and 54.9% 3,4 . Severe Acute Respiratory Syndrome Coronovirus‐2 (SARS‐CoV‐2) can induce the onset of metabolic encephalopathy in patients with COVID‐19 by a cytokine storm, hypoxemia and the direct effect on the central nervous system 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Delirium also plays a significant role in the context of older patients hospitalised for Coronavirus disease 2019 (COVID- 19) and its estimated prevalence is between 14.2% and 54.9%. 3,4 Severe Acute Respiratory Syndrome Coronovirus-2 (SARS-CoV-2) can induce the onset of metabolic encephalopathy in patients with COVID-19 by a cytokine storm, hypoxemia and the direct effect on the central nervous system. 5,6 Delirium during COVID-19 hospitalisation poses several specific challenges.…”
Section: Introductionmentioning
confidence: 99%